Foreign and domestic visitors' perceived satisfaction of the roles of nature guide at Pahang National Park, Malaysia - Hashim, Mustakim (2016)
Ecotourism in Malaysia is emerging as one of the most popular tourism niches and attracts a lot of tourists to the country. In line with its rising importance, preservative actions must also be conducted to ensure the sustainability of the ecotourism sites. Naturally, the most suitable person to deliver this objective is the nature guide as they are the front liners that meet, greet and accompany the visitors to designated sites. However, there are complaints regarding the services provided by the guides. Therefore, this study tries to explore how nature guide can play their role in order to meet the visitors’ expectations and ensure their satisfaction at the Pahang National Park (PNP). In achieving the objective, the study applies a framework based on the extended Modern Tour Guide Model (MTGM). This study explores the visitors’ expectation towards the roles played by the nature guide and simultaneously evaluates the performance of the guides. In addition, the Disconfirmation Theory was adapted as the basis to examine visitors’ satisfaction by using the discrepancies between expectation and the performance (P-E). Gap analysis was further used to examine the satisfaction level among the visitors. 384 visitors of Pahang National Park in Kuala Tahan who used the nature guide service completed the distributed questionnaires. The analyses involved in this study are the descriptive analysis, paired and independent sample T-tests, and gap analysis. Findings of this study show high expectations among the visitors of PNP and the performance of the nature guide was highly rated. Comparing the feedback from the local and foreign visitors, local visitors demonstrated higher expectations as well as higher rating for the nature guide’s performance compared to their foreign counterparts. The overall result shows the visitors of PNP are satisfied with all the roles played by the nature guides except as the motivator of responsible behaviour. The gap values for the roles that are satisfied by the visitors range from 0.39 to 0.02. The only negative value recorded is for the motivator of responsible behaviour role which is -0.07. Further investigation reveals that the roles in resource management are worthy for consideration. Therefore, results for roles involving theenvironment were not significant. These findings highlight the need for the nature guide to overcome this situation. Specific or focused training like environmental interpretation can help in improving the services of the nature guide at TNP. This kind of training can be implemented in the continuous tourism-related education (CTRE) courses that are compulsory during licenses renewal.